Hubungan Profitabilitas, Tahun Pandemi, dan Financial Distress pada Tax Avoidance - Andika, I Kadek Peri; Sukartha, P. D'yan Yaniartha (E-Jurnal Akuntansi, 2023)
The government continues to strive to optimize tax revenue, but the tax revenue target has not been achieved due to various reasons, one of which is tax evasion. The research objective is to examine the relationship between profitability, the year of the pandemic, and financial distress on tax avoidance. The research population is all issuers listed on the Indonesia Stock Exchange during the 2018-2021 period. The number of samples used is 748 companies with purposive sampling method. The research data were analyzed using multiple linear regression analysis using the Statistical Data Analysis (STATA) application. The results of the study show that profitability, the year of the pandemic and financial distress are negatively related to tax avoidance. Keywords: Profitability; Covid-19; Financial Distress; Tax Avoidance